Satisfaction of IIUM medical students towards online learning and its facilitating factors - Zamani, Muhammad Razin; Razman, Amalia Izzati; Shaik Mohd Nizam, Nur Alia Iman; Ahmad Ashhar, Muhammad Ikmal Arif; Ahmad Haridan, Ahmad Zhareff Emir; Nor Azlan, Nur Khairunnisa; Mohamad, Mohammad Muaz; Shahrir, Shahida Athirah; Anuar, Muhammad Ashraf Fithri; Johari, Muhammad Luqman ‘Afif; Zulkifli, Ahmad Najmi Abid; Abdullah, Muhammad Haikal; et al. (2021)
The declaration of COVID-19 as a pandemic on 11th March 2020 has left a significant mark on the global education ecosystem. The transition from conventional to online learning is challenging for the administrators, teachers and students. The purpose of this study is to determine the satisfaction towards online learning and its facilitating factors among medical students in the International Islamic University Malaysia (IIUM). We conducted a cross-sectional study among first- and second-year medical students in IIUM from July to August 2021. The study protocol has been approved by the institutional research committee (Research ID 735). We asked the participants to complete a web-based self-administered Online Learning Experience Questionnaire (OLEQ) and rated the items using the 4 and 5-Likert scales. We used IBM SPSS Statistics 26 (IBM, New York) to describe and analyse the data. We received 50% (n=77) and 59% (n=80) responses from first- and secondyear medical students respectively. In general, the satisfaction of the students towards online learning was positive (mean 2.84-3.87 out of 4). In both cohorts, access to information and learning material scored the highest satisfaction followed by interaction with teachers. Meanwhile, the topmost factor facilitating online learning was being encouraged to take responsibility for their learning [4.11 (0.82) out of 5] followed by electronic communication with the teacher [3.92 (0.91)]. We found a positive association between the satisfaction score towards online learning and the facilitating factors score (r=0.635, p<0.001). In a nutshell, we can see that the IIUM medical students’ satisfaction towards online learning was positive and this could be attributed to the facilitating factors. This finding could be useful for policy-makers and administrators in education to focus on these factors to keep the system relevant in this current pandemic situation.